Penerapan Pekarangan Pangan Lestari Melalui Vertikultur Pada KWT Sejati Kelurahan Aplasi, Nusa Tenggara Timur - Tobing*, Wilda Lumban; Naisali, Hyldegardis; Maulana, Achmad Subchiandi; Sipayung, Boanerges Putra; Kia, Kristoforus Wilson; Bria, Deseriana; Silla, Misail Epainetus; Talan, Veronika Sofia Jaquelin (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
Fulfillment of food can be done through the implementation of Sustainable Food Yards. KWT Sejati has difficulty providing food throughout the year. The yard owned is not productive because it has dry land biophysics with a dry climate. This condition is also a factor that influences people's food status (food insecurity). Management of dry land as agricultural land requires the adoption of technology. Verticulture technology can be used as an alternative to meet food needs in Karing. This activity aims to apply P2L to KWT Sejati through verticulture as a technology for cultivating vegetables on dry land. The method for implementing this activity is counseling and demonstration using a learning by doing system. The results of this activity provide many benefits to KWT Sejati, including: ease in managing dry land as agricultural land, being able to engineer planting media to improve soil quality, and producing higher production and income compared to using a raised bed system, and has the potential to overcome food insecurity conditions